Selected theories in gay and lesbian studies : a sociological inquiry into homosexual identity and same-sex intimacy - Adeagbo, Oluwafemi Atanda (Gender & behaviour, 2016)
Social scientists have been developing the area of gay and lesbian studies over the past four decades, perhaps since the publication of Mary McIntosh’s seminal article in 1968. Whilst McIntosh’s article addressed the homosexual role in England and described homosexuality as a social role (not a condition) that is outside of a recognised role (heterosexuality), gay and lesbian sociology has received little recognition as a distinctly sociological sub-discipline. A thriving field of ‘family sociology’ has developed internationally, but scholars in this field tend to focus more on heterosexual familial arrangements, issues and concerns. This is not to say that family sociologists have excluded gay and lesbian studies from the mainstream of family sociology. Despite the comparatively fewer studies on gay families, households and child-rearing (amongst other topics) across the globe, particularly in Africa, the importance of those studies cannot be discounted as they continue to shape and influence further research and reflection on this group in order to better understand them. Also, the ambiguity of some theories within the field of gay and lesbian studies further renders homosexual identity and same-sex unions problematic. It is against this backdrop that this paper examines some selected theories in gay and lesbian studies through sociological lens.